Pushing the detection limit of thin film magnetoelectric heterostructures. Issue 6 (22nd February 2017) - Röbisch, Volker; Salzer, Sebastian; Urs, Necdet O.; Reermann, Jens; Yarar, Erdem; Piorra, André; Kirchhof, Christine; Lage, Enno; Höft, Michael; Schmidt, Gerhard U.; Knöchel, Reinhard; McCord, Jeffrey; et al.
Abstract: Abstract : Composite magnetoelectrics implemented as thin film heterostructures are discussed in view of their applicability as highly sensitive magnetic field sensors. Here, either PZT or AlN served as piezoelectric component. The magnetostrictive phase consisted of layer systems based on FeCo or (Fe90 Co10 )78 Si12 B10 . All functional layers were deposited with thicknesses of a few micrometers on Si cantilever structures with typical lateral dimensions of 25 mm by 2.2 mm. Magnetoelectric coefficients as large as 6900 V/cm Oe and a limit of detection as low as 1 pT/(Hz) 1/2 were measured. Currently, the best result demonstrates a detection limit of 500 fT/(Hz) 1/2 at 958 Hz frequency using a set of two sensors for external noise suppression. A frequency conversion technique is proposed to broaden the applicability of resonant magnetoelectric sensors to a wider frequency range. Finally, the achieved sensor performance is evaluated with regard to typical magnetic field amplitudes in medical applications.